2002
DOI: 10.1116/1.1450580
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radio-frequency sputter-deposited textured TiN thin films as diffusion barriers between copper and silicon

Abstract: Thin textured titanium nitride (TiN) films with thicknesses under 100 nm were grown on (100) silicon wafers by employing a radio-frequency generator to sputter reactively a Ti target under poisoned modes in mixtures of fixed Ar (3.6×10−1 Pa) and N2 at various partial pressures. The texture of the TiN films can be tailored by appropriately controlling the partial pressure of the reactive nitrogen. (111) textured films can be deposited over a broad range of lower N2 partial pressures from 2.9×10−2 to 1.8×10−1 Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…[9][10][11][12] A TiN film (41-98 µ³ cm) allows low-temperature Cu diffusion at 500 °C or higher in a Cu/TiN (100 nm)/Si contact. 17,18,26,27) In a Cu/Si contact with a 50-nm-thick amorphous Ti-W-N barrier, failure of the contact occurs owing to the crystallization of the barrier, where the decomposition of Ti-W-N into TiN and W takes place after annealing at up to 700 °C for 1 h. 28) However, when the annealing temperature reaches 600 °C or higher, Ti atoms that diffused toward the Si and Cu interfaces form reaction products, e.g., CuTi x and TiSi x , at each interface. Since the resistivity of Ti-W films is relatively high (90-300 µ³ cm), 29,30) the Ti-W-N barrier will have a high resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12] A TiN film (41-98 µ³ cm) allows low-temperature Cu diffusion at 500 °C or higher in a Cu/TiN (100 nm)/Si contact. 17,18,26,27) In a Cu/Si contact with a 50-nm-thick amorphous Ti-W-N barrier, failure of the contact occurs owing to the crystallization of the barrier, where the decomposition of Ti-W-N into TiN and W takes place after annealing at up to 700 °C for 1 h. 28) However, when the annealing temperature reaches 600 °C or higher, Ti atoms that diffused toward the Si and Cu interfaces form reaction products, e.g., CuTi x and TiSi x , at each interface. Since the resistivity of Ti-W films is relatively high (90-300 µ³ cm), 29,30) the Ti-W-N barrier will have a high resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon was also observed for RF-sputtered TaN films 5 and TiN films. 44 This critical nitrogen partial pressure may be associated with the formation of NbN x on the surface of the target. As is well known, the sputtering rate depends on the sputtering yield of the target material, and the yield values of metal nitrides are generally lower than those of pure metals.…”
Section: Discussionmentioning
confidence: 99%
“…32) For comparison, we also show the characterization of TiN films reported by others. [21][22][23]35,36) Table I shows that the substrate temperature ranged from 350 °C to 400 °C for TiN film formation by the reactive sputtering method. Yee et al 37) reported that the resistivity of TiN x , ZrN x , and HfN x films formed at 200 °C is in the range of 10 2 -10 6 μΩcm, and they become insulating films when formed at lower temperatures.…”
Section: Characterization Of Metal Nitride Filmsmentioning
confidence: 99%
“…Until now, in LSI metallization, TiN and TaN films have been mainly used for Al-based metallization or Cu interconnects as candidate diffusion barrier materials. [12][13][14][15][16][17][18][19][20] These films were formed at substrate temperatures of 350 °C-400 °C, 18,[21][22][23] which was required for the metal and nitrogen atoms to react sufficiently as a nitride. However, it is necessary to lower the process temperature of LSI by introducing multilayer interconnects and low-k materials.…”
Section: Introductionmentioning
confidence: 99%